Visual Dynamics of Dots in Farsi Typography: Balancing Aesthetics and Readability - Daneshgar, Fahimeh; Kermani, Mansoor Hessami; Taheri, Faeze (Scientific Research, New Technologies and Applications Vol. 9, 2024)
Background: This paper discusses the plastic role of letter dots, as the first design element in the application of titles and slogans, deals with the plastic function of dot's place in Farsi typography looking at the methods of teaching typography at old high schools of graphic art Basel and Bauhaus by Gestalt theory approach in art. The graphic design purpose, depending on its medium is the transferring of message in the fastest and the most explicit way possible to the respondent and the tools for the messaging are visual and written elements having two visual and verbal aspects. The problem addressed in this research is that some deconstructions of typography occur in Iranian graphics, such as breaking the letters from attached to detached form, filling the gaps of circular letters, removing dots, etc., which may sometimes have a purely aesthetic purpose and distract typography from its main function, reading the verbal message. Methods: In this paper, the plastic action (direction, emphasis, balance, rotation, movement, etc.) of a dot on its place in Farsi fonts has been studied through analysis of dotted letters in the application of title and slogan in which for their larger size, dots of letters take a plastic situation- based on rules of visual arts by the approach of Gestalt theory in art. Samples were dotted letters of simple Farsi fonts that are structurally similar and accessible to graphic designers. The analysis emphasizes the detached letters and an example of ligaments as a statement. Finding: The results show that the dot's place of dotted letter, in simple Farsi font is important from the formation of regulated visual relations viewpoint and it was emphasized the non-regulated move of dots in Farsi font impairs visual relationships that dominate it. Dots in Farsi letters have two important visual roles focused dot in Farsi typography means, getting out of the visual form of a line and focusing on their role of visual emphasis in various forms, and in the linear form, two dots next to each other in a same direction can create a horizontal or vertical visual line. The purpose of this study was to achieve the plastic function of letter dots in Farsi typography to encourage designers to create a plastic challenge reasonably consistent with the message content and maintain both aesthetic and functional aspects of typography, in their graphic artwork. Conclusion: The application of this article is the need to make any changes and innovations in Farsi typography, in the context of the Cognition of the basic design that dominates them, and at the same time maintaining the ease of reading of visual message.